Identification of compounds with anti-proliferative activity against Trypanosoma brucei brucei strain 427 by a whole cell viability based HTS campaign. - Melissa L Sykes; Jonathan B Baell; Marcel Kaiser; Eric Chatelain; Sarah R Moawad; Danny Ganame; Jean-Robert Ioset; Vicky M Avery (Public Library of Science (PLoS), 2012)
Human African Trypanosomiasis (HAT) is caused by two trypanosome sub-species, Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense. Drugs available for the treatment of HAT have significant issues related to difficult administration regimes and limited efficacy across species and disease stages. Hence, there is considerable need to find new alternative and less toxic drugs. An approach to identify starting points for new drug candidates is high throughput screening (HTS) of large compound library collections. We describe the application of an Alamar Blue based, 384-well HTS assay to screen a library of 87,296 compounds against the related trypanosome subspecies, Trypanosoma brucei brucei bloodstream form lister 427. Primary hits identified against T.b. brucei were retested and the IC(50) value compounds were estimated for T.b. brucei and a mammalian cell line HEK293, to determine a selectivity index for each compound. The screening campaign identified 205 compounds with greater than 10 times selectivity against T.b. brucei. Cluster analysis of these compounds, taking into account chemical and structural properties required for drug-like compounds, afforded a panel of eight compounds for further biological analysis. These compounds had IC(50) values ranging from 0.22 µM to 4 µM with associated selectivity indices ranging from 19 to greater than 345. Further testing against T.b. rhodesiense led to the selection of 6 compounds from 5 new chemical classes with activity against the causative species of HAT, which can be considered potential candidates for HAT early drug discovery. Structure activity relationship (SAR) mining revealed components of those hit compound structures that may be important for biological activity. Four of these compounds have undergone further testing to 1) determine whether they are cidal or static in vitro at the minimum inhibitory concentration (MIC), and 2) estimate the time to kill.